Handbook of Environmental Isotope Geochemistry - Baskaran, Mark.; Baskaran, Mark. (Advances in Isotope Geochemistry,, 2012)
Applications of radioactive and stable isotopes have revolutionized our understanding of the Earth and near-earth surface processes. The utility of the isotopes are ever-increasing and our sole focus is to bring out the applications of these isotopes as tracers and chronometers to a wider audience so that they can be used as powerful tools to solve environmental problems. New developments in this field remain mostly in peer-reviewed journal articles and hence our goal is to synthesize these findings for easy reference for students, faculty, regulators in governmental and non-governmental agencies, and environmental companies. While this volume maintains its rigor in terms of its depth of knowledge and quantitative information, it contains the breadth needed for wide variety problems and applications in the environmental sciences. This volume presents all of the newer and older applications of isotopes pertaining to the environmental problems in one place that is readily accessible to readers. This book not only has the depth and rigor that is needed for academia, but it has the breadth and case studies to illustrate the utility of the isotopes in a wide variety of environments (atmosphere, oceans, lakes, rivers and streams, terrestrial environments, and sub-surface environments) and serves a large audience, from students and researchers, regulators in federal, state and local governments, and environmental companies. .